An Overview of Government Business Support Programmes For Micro and Small Businesses in Malaysia During the Covid -19 Crisis - Salmah Topimin; Siti Rahayu Mohd Hashim (Penerbit UMS, 2021)
The largest number of business establishments in Malaysia is micro and small businesses. Although micro and small businesses make a great contribution to the country’s economic development, they are vulnerable and easily affected by any changes occurring within the business environment. Therefore, to ensure the survival of micro and small businesses in Malaysia, various business support programmes have been introduced by the government. It is believed that a conducive intervention programme is significant in ensuring the survival, competitiveness and growth of micro and small businesses. However, the effectiveness of business support programmes in facilitating the business survival of micro and small businesses have been debated. With the emergence of the current COVID-19 crisis, the issue of the effectiveness of the programmes become more critical. Based on a literature review, this study explores the issues and challenges concerning the access to, utilisation and delivery of micro and small business support programmes. The reviewed literature shows that the ineffectiveness of business support programmes is related to issues and challenges in the implementation of the programmes.